2020
DOI: 10.1111/cdep.12378
|View full text |Cite
|
Sign up to set email alerts
|

From Theory to Methodology: Using Ecological Engagement to Study Development in Context

Abstract: Urie Bronfenbrenner’s groundbreaking work on development in context has made an enduring impact on the field of developmental science. However, translating his theoretical concepts in empirical studies has proved challenging. In this article, we describe a methodological approach—ecological engagement methodology (EEM)—that was designed to operationalize key elements of Bronfenbrenner’s bioecological theory in studies of development in context. In particular, we describe the development of EEM, illustrate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 44 publications
0
7
0
6
Order By: Relevance
“…Following the Ecological Engagement approach (Koller et al, 2020), children and adolescents with a history of street involvement were identified and invited to participate. Our main goal was to identify a sample with known characteristics and thus recruitment rates were not tracked.…”
Section: Methodsmentioning
confidence: 99%
“…Following the Ecological Engagement approach (Koller et al, 2020), children and adolescents with a history of street involvement were identified and invited to participate. Our main goal was to identify a sample with known characteristics and thus recruitment rates were not tracked.…”
Section: Methodsmentioning
confidence: 99%
“…The school is an essential microsystem for student development. According to the Bioecological Theory of Human Development, a microsystem is an immediate context in which individuals play an active role and promote their development (Leme et al, 2015;Koller et al, 2020).…”
Section: Rendimiento Académico En El Primer Y Tercer Grados Escolar: ...mentioning
confidence: 99%
“…O contexto escolar pode ser considerado um microssistema importante para o desenvolvimento dos estudantes. De acordo com a Teoria Bioecológica do Desenvolvimento Humano, o microssistema refere-se ao contexto imediato no qual a pessoa inserida participa ativamente, de modo a promover o próprio desenvolvimento (Leme et al, 2015;Koller et al, 2020).…”
Section: Rendimiento Académico En El Primer Y Tercer Grados: Un Estud...unclassified